2018
DOI: 10.3174/ajnr.a5782
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic-Pathologic Correlation of Tumor Thickness and Its Prognostic Importance in Squamous Cell Carcinoma of the Oral Cavity: Implications for the Eighth Edition Tumor, Node, Metastasis Classification

Abstract: This study demonstrates a good radiologic-pathologic tumor thickness correlation. Intrarater and interrater reliability for radiologic tumor thickness was excellent. Radiologically thicker tumor was predictive of inferior survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 22 publications
0
32
1
Order By: Relevance
“…This study included only at tumors in which the mucosal plane was at the same level as the tumor. Then the pathologic depth of invasion and tumor thickness could be measured identically (pDOI = pTT) [13]. One experienced pathologist who was unaware of the MRI ndings oriented the specimen and routinely performedmeasurement on tumor depth of invasion.Only pathologic thicknessin the axial view was available in our institution during the study period.…”
Section: Mri and Pathologic Parameters Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…This study included only at tumors in which the mucosal plane was at the same level as the tumor. Then the pathologic depth of invasion and tumor thickness could be measured identically (pDOI = pTT) [13]. One experienced pathologist who was unaware of the MRI ndings oriented the specimen and routinely performedmeasurement on tumor depth of invasion.Only pathologic thicknessin the axial view was available in our institution during the study period.…”
Section: Mri and Pathologic Parameters Measurementmentioning
confidence: 99%
“…There are severalimaging methods available for preoperative evaluation.More recent studies suggest that the high resolution of magnetic resonance imaging (MRI) is reliable optimally depicts soft tissue tumor extension, and is useful to assess tumor thickness in predicting cervical lymph node metastasis [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This study included only at tumors in which the mucosal plane was at the same level as the tumor. Then the pathologic depth of invasion and tumor thickness could be measured identically (pDOI = pTT) [13]. One experienced pathologist who was unaware of the MRI ndings oriented the specimen and routinely performed measurement on tumor depth of invasion.…”
Section: Primary and Validation Cohortsmentioning
confidence: 99%
“…There are several imaging methods available for preoperative evaluation. More recent studies suggest that the high resolution of magnetic resonance imaging (MRI) is reliable optimally depicts soft tissue tumor extension, and is useful to assess tumor thickness in predicting cervical lymph node metastasis [11][12][13]. Previous studies have reported that MRI-assessed tumor thickness is correlated strongly and directly with pathologic thickness [14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…This study included only at tumors in which the mucosal plane was at the same level as the tumor. The pathologic depth of invasion and tumor thickness could then be measured identically (pDOI = pTT) [13]. An oral pathologist, who was unaware of the MRI ndings, oriented the specimen and routinely performed measurement on tumor depth of invasion.…”
Section: Primary and Validation Cohortsmentioning
confidence: 99%